Nutritional functions and antioxidative enzymes in juice extract from two different maturity stages of low temperature stored phalsa (Grewia subinaequalis D.C.) fruit. (January 2022) - Hassan, Hamad; Amin, Muhammad; Rajwana, Ishtiaq Ahmad; Ullah, Sami; Razzaq, Kashif; Faried, Hafiz Nazar; Akhtar, Gulzar; Naeem-Ullah, Unsar; Qayyum, Mirza Abdul; Aslam, Muhammad Majid; Ali, Kashif; Asghar, Zohaib; et al.
Abstract: Phalsa is an important berry fruit in Asia, but little is known of its postharvest characteristics and especially changes in fruit composition during storage. Investigations were made for nutritional and antioxidative enzymatic changes in the juice extracted from two different maturity stages (M1 : pink to red or M2 : dark red to purple) during low temperature storage for 0, 2, 4, 6, 8 and 10 days at 5 ± 1 °C and 65 ± 5% RH. The fruit showed significant gradual declines in ascorbic acid (Vitamin C), total phenolics (TPC), total antioxidant capacity (TAC), total carotenoids, anthocyanins, moisture%, crude protein, crude fiber and fat content and the activity of superoxide dismutase (SOD) during storage. However, the total soluble solids (TSS), pH, ash content, and the activity of catalase (CAT) and peroxidase (POD) increased significantly. The polynomial regression analysis indicated that these changes were either quadratic or linear; and the Pearson's correlation among the studied parameters was significant. More mature fruit had higher concentrations of TSS, ascorbic acid, TPC, TAC, total carotenoids and anthocyanins, more juice and less weight-loss compared with less mature fruit. Overall, significant nutritive functions and antioxidative enzymes were found in both maturity stages of phalsa fruit, which experienced significant changes during postharvest storage. Highlights: The juice of ripe phalsa fruit has better nutritional properties than early mature. Various biochemicals, bioactive compounds and natural pigments in phalsa juice significantly reduce under storage. The proximate composition of phalsa fruit juice is influenced by fruit harvest maturity and low temperature storage. POD enzyme activity in phalsa fruit juice increases while SOD and CAT decline during storage.